2016
DOI: 10.4149/bll_2016_019
|View full text |Cite
|
Sign up to set email alerts
|

Exercise improves hippocampal estrogen and spatial memory of ovariectomized rats

Abstract: OBJECTIVE: The present study aimed at examining the effects of regular exercise on hippocampal estrogen and estrogen receptor β (ERβ) levels, as well as the spatial memory of ovariectomized rats. BACKGROUND: A decrease of estrogen levels leads to dysfunctions of hippocampus, including spatial learning and memory. Studies have shown that physical exercise improved spatial memory of ovariectomized rats and was associated with an increased extragonadal aromatization. This in turn affects the expression of estroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
0
8
1
2
Order By: Relevance
“…In addition, the present study didn’t show any significant change in working and reference memory assessed by MWM after aerobic exercise in OVX groups with different status of Vit D. However study carried out by Kaidah et al [ 58 ] showed contradictory result [ 58 ]. Inconsistency might be related to difference in exercise protocols which consisted of five times per week for 12 weeks in ovariectomized rats in their work [ 58 ].…”
Section: Discussioncontrasting
confidence: 72%
“…In addition, the present study didn’t show any significant change in working and reference memory assessed by MWM after aerobic exercise in OVX groups with different status of Vit D. However study carried out by Kaidah et al [ 58 ] showed contradictory result [ 58 ]. Inconsistency might be related to difference in exercise protocols which consisted of five times per week for 12 weeks in ovariectomized rats in their work [ 58 ].…”
Section: Discussioncontrasting
confidence: 72%
“…Unlike controls, training reversed cell death in LDL-OT group significantly, approaching its rate than sedentary control group (CS). Kaidah et al 30 also verified this action of physical activity in the hippocampus of ovariectomized rats trained. Comparing the wild groups and knockout, it can infer that the effect of physical activity on cell death may depend on the oxidative stress of the tissue level.…”
Section: Discussionmentioning
confidence: 86%
“…Estrogen is a steroid hormone mainly produced by the ovaries and primarily known for its role in the achievement of sexual maturation and fertility. Apart from its commonly known roles, estrogen also stimulates neuroprotective mechanisms that lead to the improvement of both neuronal health and spatial memory retention (8,16). These neuroprotective properties of estrogen are typically facilitated by its most biologically active form, estradiol (17,18).…”
Section: Estrogen and The Brainmentioning
confidence: 99%